2020
DOI: 10.3390/microorganisms8121949
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Functional Traits of Lactobacilli from Women with Asymptomatic Bacterial Vaginosis and Normal Microbiota

Abstract: Asymptomatic bacterial vaginosis (BV) in reproductive-age women has serious obstetric and gynecological consequences. Despite its high incidence, the behavior of vaginal lactobacilli in asymptomatic BV is unknown. We analyzed the functional properties of previously isolated vaginal lactobacilli from asymptomatic women with normal, intermediate, and BV microbiota. Lactic acid and antimicrobial activity against seven urogenital pathogens were evaluated from lactobacilli cell-free culture supernatants (CFCs) (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
(29 reference statements)
0
8
1
1
Order By: Relevance
“…Though all species exerted antiproliferative effect on cervical cells, selective species were more efficient in their cytotoxicity. Our studies including that of others ( Chuah et al, 2019 , Happel et al, 2020 , Pramanick and Aranha, 2020 Dec 9 ) have demonstrated different strains of the same species also vary in their functional properties, hence investigation of several species need to be undertaken to identify the promising probiotic for particular function. Studies have shown that probiotics isolated from different environments or from the same environmental niche have varying functional properties (( Bazireh et al, 2020 , Kahraman et al, 2022 ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Though all species exerted antiproliferative effect on cervical cells, selective species were more efficient in their cytotoxicity. Our studies including that of others ( Chuah et al, 2019 , Happel et al, 2020 , Pramanick and Aranha, 2020 Dec 9 ) have demonstrated different strains of the same species also vary in their functional properties, hence investigation of several species need to be undertaken to identify the promising probiotic for particular function. Studies have shown that probiotics isolated from different environments or from the same environmental niche have varying functional properties (( Bazireh et al, 2020 , Kahraman et al, 2022 ).…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, HPV is implicated in cervical, anal and oropharyngeal cancers ( Schiffman et al, 2016 ). L. salivarius and L. vaginalis are the microbiota commonly identified in the vagina of healthy women and known to play a protective role against urogenital infections ( Madhivanan et al, 2014 , Pino et al, 2019 , Pramanick and Aranha, 2020 Dec 9 ). So it would be interesting to evaluate the indigenous microbiota of healthy individuals for their protective activity against HPV cancers of oral and cervico-vaginal origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the vaginal microbiota dominated by L. crispatus , which produces more lactic acid than L. iners , is thought to be more advantageous for keeping the vagina at a low pH level ( Pramanick and Aranha, 2020 ; Adapen et al., 2022 ; Argentini et al., 2022 ). L. crispatus is related to defense against infections and regulates anti-inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%